1847 Ga. Laws 138 - (:unkn) unknown (My University, 1847)
An Act To Incorporate The Evergreen Cemetery Company Of Bonaventure, § 5: Prohibited shooting or discharging any gun or other firearms within the cemetery limits. Violators guilty of a misdemeanor.
Keywords: DISCHARGE